Effects of Second Language Usage on Genetic Counseling Training and Supervision. Issue 1 (31st May 2012) - Vanneste, Rachel; Chiu, Sui Mei; Russell, Laura; Fitzpatrick, Jennifer
Abstract: We conducted an exploratory study of the experiences of genetic counselors who have either trained or supervised in a second language to assess the relevance of this issue to genetic counseling training and supervision. Two hundred‐thirty NSGC members, CAGC members and genetic counseling students completed the online questionnaire. Many of the respondents reported that training and supervision differed when another language was involved. Supervisors reported difficulty in assessing students' counseling skills and discomfort with an incomplete understanding of session content. Students described a greater focus on vocabulary at the expense of psychosocial dimensions. Despite this, most felt that using another language enhanced their training experience. As such, training programs might consider increasing support to these learners and supervisors by explicitly acknowledging the challenges they face, providing students with language tools to aid in their acquisition of basic skills and providing supervisors with new methods for assessing student counseling skills when using other languages.